Construction of 3‐Dimensional Printed Ultrasound Phantoms With Wall‐less Vessels. (9th May 2016) - Nikitichev, Daniil I.; Barburas, Anamaria; McPherson, Kirstie; Mari, Jean-Martial; West, Simeon J.; Desjardins, Adrien E.
Abstract : Ultrasound phantoms are invaluable as training tools for vascular access procedures. We developed ultrasound phantoms with wall‐less vessels using 3‐dimensional printed chambers. Agar was used as a soft tissue–mimicking material, and the wall‐less vessels were created with rods that were retracted after the agar was set. The chambers had integrated luer connectors to allow for fluid injections with clinical syringes. Several variations on this design are presented, which include branched and stenotic vessels. The results show that 3‐dimensional printing can be well suited to the construction of wall‐less ultrasound phantoms, with designs that can be readily customized and shared electronically.